Implications of uncertainty in true metabolizable energy estimates for estimating wintering waterfowl carrying capacities - Mark C. Livolsi; Kevin M. Ringelman; John M. Coluccy; Matthew T. Dibona; Christopher K. Williams (Wildlife Society Bulletin)
ABSTRACT Carrying capacity models for wintering waterfowl require estimates of energy availability based on food densities and true metabolizable energy (TME) of various food types. However, because TME values vary widely between studies, estimates of carrying capacity may be less precise than previously acknowledged. We explored how variation in TME values affected estimates of landscape‐level energy availability for American black ducks (Anas rubripes), using 4 distinct approaches for assigning TME values to waterfowl food items collected over the winter period in 2011–2012 and 2012–2013: a “best practices” approach, which typically used average TMEs across species, a minimum and maximum reported values approaches, and a coarse‐scale “order‐average” approach. We found that all 4 approaches yielded significantly different estimates of energy availability across all saltmarsh habitat types. Additionally, we evaluated the potential management implications of variation in TME values by comparing energy supply on 1,223 ha of marsh in Prime Hook National Wildlife Refuge (DE, USA) using all 4 approaches for assigning TME values. We estimated carrying capacity and modeled depletion of energy on this refuge over a hypothetical wintering period. We found that even relatively small variations in TME values produced highly variable estimates of carrying capacity for the refuge. Thus, we recommend that researchers consider the inherent uncertainty in TME values of waterfowl foods, and explicitly include this variation in carrying capacity models. © 2015 The Wildlife Society.